Implementation of Problem Based Learning Model to Improve Critical Thinking Skills on Asthma’ul Husna - Mukhamad Farid Ma'ruf; Zainudin Hasan (Research Journal on Teacher Professional Development, 2024)
This study aims to determine the extent to which the use of Problem Based Learning method to improve Critical Thinking Skills of Asthma’ul Husna Class 4B SDN Tambakaji 01. The formulation of the problem is How high is the increase in critical thinking skills of students in class 4B SDN Tambakaji 01 in the subject of Islamic Religious Education and Ethics material Asthma’ul Husna using the Problem Based Learning (PBL) learning model? How can the Problem Based Learning (PBL) learning model improve the critical thinking skills of students in class 4B SDN Tambakaji 01 in learning activities of Islamic Religious Education and Ethics material Asthma’ul Husna ? Collaborators in this class action research are Senior PAI Teacher Peers. This research is a Classroom Action Research consisting of 2 cycles, each cycle consisting of 4 stages, namely planning, implementation, observation, and reflection. The data collection methods used were observation and documentation. Data analysis in this study is by comparing the achievement of grades with criteria for achievement of learning objectives 70-75 and is characterized by an increase in the Classical Completeness Criteria in each cycle. Data collection is done by looking at the critical thinking skills of students during learning activities. From the analysis of the data obtained, it can be concluded that there is an increase in the critical thinking skills of students in the pre-cycle, cycle I and cycle II shows that the critical thinking skills of students have increased, students with scores below Criteria for Achievement of Learning Objectives in the pre-cycle were 52%, in cycle I decreased to 26%, cycle II decreased to 0%. So there is an increase in students in critical thinking skills from 48% to 74%, or an increase of 100%. With this increase, it has shown success in this classroom action research. The classroom action research target on improving critical thinking skills has shown the planned results, namely 85% of active students in the implementation of learning in Cycle II